SINTESIS DAN KARAKTERISASI NANOPARTIKEL Fe2O3 DARI PASIR ALAM DESA LOGAS KABUPATEN KUANTAN SINGINGI - Meilan Sihombing; Erwin Amiruddin (Komunikasi Fisika Indonesia, 2020)
Determination of magnetic and structural properties of natural sand from Logas Village, Kuantan Singingi have been carried out using a magnetic Probe Pasco PS-2162 and X-Ray Diffraction methode. Samples were synthesized using multi step ball milling methode for 90 and 90+30 hours. Results show that the magneticsuceptibility increased with increasing of ball milling time, from 90 hours to 90+30 hours. This magnetic suceptibility within the interval (46-80000) x 10-8 m3/kg which is the interval of Ilminite mineral (FeTiO3; Antiferromagnetic). X-Ray Fluorescence result showed that the composition of Fe and Ti increased after milled for 90+30 hours, while other element like Si decreased. The XRD result confirmed that the phase of the sample structure is Hematite (α-Fe2O3). However, some other phases including SiO2 and FeTiO3 are observed in diffraction pattern. This indicates that the sample is not purely hematite.